2022
DOI: 10.1002/tax.12648
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics and a revised tribal classification of subfamily Dipterocarpoideae (Dipterocarpaceae)

Abstract: Dipterocarpoideae, the largest subfamily in the Meranti family (Dipterocarpaceae) are an ecologically dominant group of trees throughout much of wet tropical Asia. Increasing anthropogenic pressures on this economically important tree family make it essential to resolve their complex evolutionary relationships and understand the distribution of genetic diversity throughout the family and distribution range. Dipterocarpaceae have been the focal group in a wide range of studies, owing to their economic value, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 130 publications
(240 reference statements)
3
4
0
Order By: Relevance
“…Our divergence time analysis also suggests that the diversification of major lineages of Stictopterinae began in the Middle Miocene (12–14 Ma). These estimates are similar to those recovered in divergence time estimates for the age of Dipterocarpaceae (Cvetković et al, 2022), which suggested that species diversification began in the Late Oligocene–Early Miocene (21–27 Ma).…”
Section: Discussionsupporting
confidence: 87%
“…Our divergence time analysis also suggests that the diversification of major lineages of Stictopterinae began in the Middle Miocene (12–14 Ma). These estimates are similar to those recovered in divergence time estimates for the age of Dipterocarpaceae (Cvetković et al, 2022), which suggested that species diversification began in the Late Oligocene–Early Miocene (21–27 Ma).…”
Section: Discussionsupporting
confidence: 87%
“…Our time of divergence analysis also revealed that the diversification of major generic lineages of Stictopterinae appears to have begun approximately in Middle Miocene (12–14 my). These estimates are similar to those recovered in phylogenomic divergence time estimations of Dipterocarpaceae (Cvetković et al, 2022), which suggested a species diversification from the Late Oligocene–Early Miocene (21–27 my) in most lineages except for Richetioides (Middle Miocene 14.05 my). The reconstruction of ancestral character states for host-plants pairs several genera with Fabales.…”
Section: Discussionsupporting
confidence: 85%
“…Our time of divergence analysis also revealed that the diversification of major generic lineages of Stictopterinae appears to have begun approximately in Middle Miocene (12-14 my). These estimates are similar to those recovered in phylogenomic divergence time estimations of Dipterocarpaceae (Cvetković et al, 2022)…”
Section: Hostplant Associations and Divergence Time Of Major Lineages...supporting
confidence: 85%
See 1 more Smart Citation
“…A few comments on dipterocarp origins are warranted in light of recent reviews of this fascinating topic ( Kooyman et al, 2019 ; Ashton et al, 2021 ; Cvetković et al, 2022 ). The dipterocarps are widely held to have originated on the supercontinent of Gondwana and to have arrived in Asia via the post-Gondwanan movements of India or Africa ( e.g ., Ashton et al, 2021 and references therein).…”
Section: Discussionmentioning
confidence: 99%